Promoting Mobile Payment with Price Incentives - Ho, Chun-Yu; Kim, Nayoung; Rong, Ying; Tian, Xin (Management Science, 2022)
Using a proprietary data set containing more than 10 million transactions over 14 months from hundreds of grocery stores, we examine consumer payment choices at point of sale (POS) between cash and mobile, where the use of other methods (including cards) is minimal. We find that cash is the dominant method of payment. Nonetheless, the share of mobile payments has increased at the expense of cash payments over time. Importantly, we exploit price incentives for consumers using mobile payment to examine the price substitution between cash and mobile payments. Our results show that consumers are more likely to use mobile payment when they receive price incentives for doing so, and such an effect persists for a few days, even after the price incentive expires. Nonetheless, the price incentives are unlikely financed by additional transactions paid via mobile but subsidized by mobile payment providers. Interestingly, we find several factors that enhance and supplement the steering effect of price incentives. First, a larger monetary reward seems to induce a stronger impact of price incentive on mobile payment. Second, the steering effect of price incentive is stronger for stores that serve consumers who have frequently been using mobile payment and for price-sensitive consumers. Third, the additional mobile payments come from transactions that would not have occurred with price incentive and those that switch from cash transactions. This paper was accepted by Eric Anderson, marketing.